Scale to measure the emotional connection with a tourist destination - Torres Moraga, Eduardo; Vidal Buitano, Agustín; Soto Sanhueza, Luis (Estudios de Administración, 2020)
This research aims to propose a scale of love for a tourist destination, which allows a more comprehensive understanding of the emotional connection between tourists and the places they visit. Through a process of content validity, the dimensions of affection, passion, identity, dependence and integration were defined as part of the love of a tourist destination construct. Through a survey, the participants evaluated the items of these dimensions, based on the tourist destination with which they felt emotionally linked. The results show that these five dimensions are indeed part of a valid and reliable scale that could be used as an approximation to measure love towards a tourist destination.